ANALISIS FAKTOR RISIKO YANG MEMPENGARUHI KEJADIAN ANEMIA PADA PETANI DI DESA LINGGASARI KABUPATEN BANYUMAS - Radi, Radi; Rejeki, Dwi Sarwani Sri; Octaviana, Devi (Jurnal Kesehatan Masyarakat, 2024)
Anemia is one of the non-communicable diseases that causes anemia sufferers to experience symptoms in the form of pallor, lethargy, dizziness or headache, and firefly eyes. The incidence of anemia worldwide is still high, it is estimated that as many as 1.3 billion people in the world suffer from anemia with a prevalence of 32.9% in 2018. Anemia in farmers is one of the health problems experienced by the residents of Linggasari Village, the incidence of anemia in farmers can be caused by various factors such as environmental factors and nutritional intake factors. The researcher intends to determine the risk factors for the incidence of anemia in farmers in Linggasari Village, Banyumas Regency. The purpose of this study was to analyze the influence of variables of education, income, length of service, history of pesticide exposure, use of PPE, nutrient intake, and helminthiasis on the incidence of anemia in farmers. This research method is quantitative research with a control case approach. The results of the analysis showed that the variable use of PPE was the most influencing factor in the incidence of anemia in farmers p value 0.023 OR 4.817 (1.247 – 18.605). Variables that do not affect the incidence of anemia in farmers are vairabel income  p value 0.854, education p value 0.654, service period p value 0.608, nutrient intake p  value 0.563, history of pesticide exposure p value 0.508,   and disability p value  0.070).